The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1590/1980-5373-mr-2017-0990
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Potential Deposition on the Parameters of ZnO dye-sensitized Solar Cells

Abstract: Dye-sensitized solar cells (DSSCs) are a feasible option for photovoltaic energy. Zinc oxide is an n-type semiconductor employed as photoanode on DSSCs. ZnO thin films were electrodeposited to study the effects of different potentials applied during deposition. SEM images, XRD and UV-Vis analysis were conducted to reveal the morphologic, structural and optical properties of the films at three potentials. DSSCs were assembled and the photovoltaic parameters were obtained through J-V plots. DSSC with 0.031% of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…In this case, the betacyanin pigment would act as the sensitizer. The values of the bandgap energy in this work were close to other reported ZnO dye-sensitized solar cells [21] and natural pigment-modified ZnO materials prepared from laali [22].…”
Section: Characterization Of Composite Materialssupporting
confidence: 89%
“…In this case, the betacyanin pigment would act as the sensitizer. The values of the bandgap energy in this work were close to other reported ZnO dye-sensitized solar cells [21] and natural pigment-modified ZnO materials prepared from laali [22].…”
Section: Characterization Of Composite Materialssupporting
confidence: 89%
“…Nunes et al employed the ZnO nanorods prepared by electrochemical methods for the DSSC and reported as much as 0.31% efficiency. However, the lower value of the efficiency was attributed to the carriers recombination owing to the non‐uniformity of the FTO substrate [3]. Tanmoy et al prepared and studied the DSSC based on the sulphur/nitrogen co‐doped graphene dot decorated ZnO nanorods and reported 0.293% cell efficiency [24].…”
Section: Resultsmentioning
confidence: 99%
“…Further, the growth of ZnO nanostructures can be controlled using the electrochemical process parameters, such as deposition time, applied potential, molar concentration, oxygen flow, and bath temperatures. Nunes et al [3] presented the preparation of ZnO nanorods by varying the negative potential from −1.4 to −0.5 V and employed as a photoanode material in DSSCs. Scanning electron microscopy (SEM) study confirmed the preparation of nanosheets with nodular structure by varying the applied potential.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc oxide is an environmentally safe material, as it has a high binding energy at room temperature (60 meV) and also has a large direct energy gap (3.37 eV) [1][2][3] and thus can be used in various hardware applications , such as solar cells , smart windows, gas sensors, piezoelectric transducers, transparent high power electronics, varistors, and ultraviolet (UV) light-emitters [4][5][6] . Sub-Extra energy levels will be generated in the band gap of the semiconductors when it is doped with metal 7,8 .…”
Section: Introductionmentioning
confidence: 99%